A review of untreated household greywater quality to inform the water saving-risk trade-off in South Africa - Nel, Nicole; Brink, Isobel; Jacobs, Heinz Erasmus; Ilemobade, Adesola (Water S. A., 2022)
Interest in greywater reuse is increasing in South Africa, because of the potential to supplement scarce freshwater resources in the face of increasing demand and aridity. This paper aims to inform the water savingrisk trade-off associated with residential untreated greywater use, through a statistical analysis of greywater quality results as sourced from prior South African studies. Greywater sources included in this review were the bathroom, kitchen, laundry, mixed and general residential sources. Variability in terms of each of the reported physical, chemical and microbiological constituents by source and between result sets was noted. Statistically significant differences were evident between the pH, conductivity and phosphorus values of certain sources. A risk assessment undertaken for each of the constituents revealed further variability. The constituent with the highest number of high-risk samples was total dissolved solids. The relatively high risk and negative consequences in greywater practices in terms of public health, the environment, and infrastructure, given this variability, provide insight into the trade-off with potential water savings. It is recommended that a more nuanced view of the potential potable savings associated with greywater reuse and also improved risk management is required by the user. KEYWORDS greywater risk quality